2011
DOI: 10.2140/agt.2011.11.2861
|View full text |Cite
|
Sign up to set email alerts
|

On the derivation algebra of the free Lie algebra and trace maps

Abstract: 2861On the derivation algebra of the free Lie algebra and trace maps NAOYA ENOMOTO TAKAO SATOHWe mainly study the derivation algebra of the free Lie algebra and the Chen Lie algebra generated by the abelianization H of a free group, and trace maps. To begin with, we give the irreducible decomposition of the derivation algebra as a GL.n; Q/-module via the Schur-Weyl duality and some tensor product theorems for GL.n; Q/. Using them, we calculate the irreducible decomposition of the images of the Johnson homomorp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…Using Bryant and Gupta's generators and some relations among them, we showed Proposition 9.6 (Enomoto and Satoh, [16]). For k ≥ 3, n ≥ k − 1 and l ≥ 3,…”
Section: Twisted Cohomology Groupsmentioning
confidence: 95%
See 4 more Smart Citations
“…Using Bryant and Gupta's generators and some relations among them, we showed Proposition 9.6 (Enomoto and Satoh, [16]). For k ≥ 3, n ≥ k − 1 and l ≥ 3,…”
Section: Twisted Cohomology Groupsmentioning
confidence: 95%
“…We remark that recently we [16] showed that the multiplicity of the Morita obstruction The goal of this subsection is to give an upper bound on Coker(τ k,Q ) as a GL(n, Q)-module. In order to do this, we consider the Johnson homomorphism…”
Section: Morita's Trace Mapsmentioning
confidence: 99%
See 3 more Smart Citations